WHEN GROUP WORK IS NOT COLLABORATION: A MIXED-METHODS INVESTIGATION OF ELEMENTARY STUDENTS’ COLLABORATIVE SKILLS AND TEACHERS’ PEDAGOGICAL PRACTICES - Dadan Setiawan; Bunyamin Maftuh; Ernawulan Syaodih; Arie Rakhmat Riyadi (JMIE (Journal of Madrasah Ibtidaiyah Education), 2026)
This study aims to identify elementary students' collaborative skill profiles, analyze teachers' pedagogical practices in facilitating collaboration, and explore relationships between students' collaborative competencies and teachers' instructional approaches in social learning contexts. Employing sequential explanatory mixed-methods design, the research involved 132 fifth-grade students and three purposively selected teachers from five public elementary schools in Cirebon, West Java, Indonesia. Data were collected through systematic classroom observations, student self-assessment surveys utilizing instruments adapted from Partnership for 21st Century Learning framework (Cronbach's α=0.87), and semi-structured teacher interviews. Quantitative data underwent descriptive and inferential statistical analyses, while qualitative data were analyzed using Braun and Clarke's six-phase thematic analysis. Integration employed joint display matrices generating meta-inferences. Findings reveal students' collaborative skills remain at moderate levels (M=1.93, SD=0.219), with shared responsibility constituting the weakest dimension (M=1.66). Gender demonstrates no significant effect across all dimensions (p>0.05). Qualitative analysis exposes instructional practices as pseudo-collaboration, group activities lacking essential structural elements including role differentiation, positive interdependence, and individual accountability. This pedagogical insufficiency originates from systemic deficiencies: inadequate professional development, conceptual confusion between grouping and structured collaboration, and institutional contradictions between competency mandates and content-coverage pressures. Implications necessitate transformative interventions in teacher professional development, instructional design incorporating collaborative structures, and assessment systems capturing collaborative processes and individual contributions.